Integrating Indigenous Knowledge into Early Childhood Education Curricula in Nigeria: Implications for Learning and Cultural Sustainability - Oluwasegun Samuel Kolade (Institut Kristen Teologi REAL Batam, 2026)
Early Childhood Education (ECE) in Nigeria has historically been rooted in indigenous knowledge systems transmitted through oral traditions, storytelling, songs, proverbs, and communal play. Despite policy recognition of cultural relevance, classroom practice continues to prioritize standardized, Western-oriented curricula, creating a disconnect between children's cultural environments and their formal learning experiences. This study examines how indigenous knowledge and cultural practices are integrated into early childhood education curricula in Nigeria, with a focus on classroom practices, teacher perceptions, and pedagogical implications. Grounded in Vygotsky's socio-cultural learning theory and the culturally responsive pedagogy frameworks of Ladson-Billings and Gay, the study adopts a qualitative design. Data were collected through classroom observations, semi-structured interviews with early childhood educators, and analysis of curriculum documents, and analyzed thematically. Findings reveal that while teachers occasionally incorporate indigenous stories, songs, games, and proverbs into classroom activities, such integration remains inconsistent and largely dependent on individual teacher initiative rather than systematic curriculum design. Children demonstrated markedly higher engagement and participation during culturally grounded activities. Key constraints include inadequate professional development in culturally responsive pedagogy, limited availability of culturally relevant instructional materials, and rigid adherence to standardized curricula. The study concludes that sustainable integration of indigenous knowledge into ECE requires systematic curriculum reform, targeted teacher training, and stronger home–school collaboration to support both learning outcomes and cultural continuity. Keywords: cultural sustainability; culturally responsive pedagogy; curriculum integration Nigeria; early childhood education; indigenous knowledge Abstrak Pendidikan Anak Usia Dini (PAUD) di Nigeria secara historis berakar pada sistem pengetahuan lokal yang diwariskan melalui tradisi lisan, bercerita, nyanyian, peribahasa, dan permainan komunal. Meskipun relevansi budaya telah diakui dalam kebijakan pendidikan, praktik di kelas masih cenderung mengutamakan kurikulum terstandarisasi yang berorientasi Barat, sehingga menciptakan kesenjangan antara lingkungan budaya anak dan pengalaman belajar formal mereka. Studi ini mengkaji bagaimana pengetahuan lokal dan praktik budaya diintegrasikan ke dalam kurikulum PAUD di Nigeria, dengan fokus pada praktik pembelajaran di kelas, persepsi guru, dan implikasi pedagogis. Berlandaskan teori pembelajaran sosio-kultural Vygotsky serta kerangka pedagogi responsif budaya dari Ladson-Billings dan Gay, penelitian ini menggunakan desain kualitatif. Data dikumpulkan melalui observasi kelas, wawancara semi-terstruktur dengan pendidik PAUD, dan analisis dokumen kurikulum, kemudian dianalisis secara tematik. Temuan menunjukkan bahwa meskipun guru sesekali memasukkan cerita, lagu, permainan, dan peribahasa lokal ke dalam kegiatan kelas, integrasi tersebut masih bersifat tidak konsisten dan sangat bergantung pada inisiatif individu guru, bukan pada rancangan kurikulum yang sistematis. Anak-anak menunjukkan keterlibatan dan partisipasi yang jauh lebih tinggi selama kegiatan yang berbasis budaya. Kendala utama meliputi kurangnya pengembangan profesional dalam pedagogi responsif budaya, terbatasnya ketersediaan bahan ajar yang relevan secara budaya, dan dominasi kurikulum terstandarisasi yang kaku. Studi ini menyimpulkan bahwa integrasi pengetahuan lokal yang berkelanjutan dalam PAUD memerlukan reformasi kurikulum yang sistematis, pelatihan guru yang terarah, serta kolaborasi yang lebih kuat antara sekolah dan keluarga guna mendukung hasil belajar sekaligus keberlangsungan budaya. Kata Kunci: integrasi kurikulum Nigeria; keberlanjutan budaya;pedagogi responsif budaya; pendidikan anak usia dini; pengetahuan lokal